Impact of “Time-From-Biopsy-to-Prostatectomy” on Adverse Oncological Results in Patients With Intermediate and High-Risk Prostate Cancer - Engl, Tobias; Mandel, Philipp; Hoeh, Benedikt; Preisser, Felix; Wenzel, Mike; Humke, Clara; Welte, Maria; Köllermann, Jens; Wild, Peter; Deuker, Marina; Kluth, Luis A.; Roos, Frederik C.; et al. (Frontiers in Surgery, 2020)
Abstract Objective: Many patients with localized prostate cancer (PCa) do not immediately undergo radical prostatectomy (RP) after biopsy confirmation. The aim of this study was to investigate the influence of “time-from-biopsy-to- prostatectomy” on adverse pathological outcomes. Materials and Methods: Between January 2014 and December 2019, 437 patients with intermediate – and high risk PCa who underwent RP were retrospectively identified within our prospective institutional database. For the aim of our study, we focused on patients with intermediate- (n=285) and high-risk (n=151) PCa using D’Amico risk stratification. Endpoints were adverse pathological outcomes and proportion of nerve-sparing procedures after RP stratified by “time-from-biopsy-to-prostatectomy”: ≤3 months vs >3 and < 6 months. Medians and interquartile ranges (IQR) were reported for continuously coded variables. The chi-square test examined the statistical significance of the differences in proportions while the Kruskal-Wallis test was used to examine differences in medians. multivariable (ordered) logistic regressions, analysing the impact of time between diagnosis and prostatectomy, were separately run for all relevant outcome variables (ISUP specimen, margin status, pathological stage, pathological nodal status, LVI, perineural invasion, nerve-sparing). Results: We observed no difference between patients undergoing RP ≤3 months vs >3 and < 6 months after diagnosis for the following oncological endpoints: pT-stage, ISUP grading, probability of a positive surgical margin, probability of lymph node invasion (LNI), lymphovascular invasion (LVI) and perineural invasion (pn) in patients with intermediate- and high-risk PCa. Likewise, the rates of nerve sparing procedures were 84.3 vs. 87.4% (p=0.778) and 61.0% vs. 78.8% (p=0.211), for intermediate- and high-risk PCa patients undergoing surgery after ≤3 months vs >3 and < 6 months, respectively. In multivariable adjusted analyses, a time to surgery > 3 months did not significantly worsen any of the outcome variables in patients with intermediate- or high-risk PCa (all p>0.05). Conclusion: A “time-from-biopsy-to-prostatetcomy” of >3 and < 6 months is neither associated with adverse pathological outcomes nor poorer chances of nerve sparing RP in intermediate- and high-risk PCa patients.